Dramatic response of intravenous lidocaine in a patient with status like SUNA - Debashish Chowdhury; Ashish Duggal; Arun Koul; Ankur Gupta (SAGE Publishing, 2018)
Short-lasting unilateral neuralgiform headache attacks with conjunctival injection and tearing (SUNCT) and short-lasting unilateral neuralgiform headache attacks with cranial autonomic symptoms (SUNA) are rare primary headaches that can sometimes present with a status like pattern which can be highly disabling. Intravenous (IV) lidocaine has been reported to be useful in status like SUNCT but its use in status like SUNA remains unexplored. We report a patient of episodic SUNA who despite on multiple conventional drugs had status like presentation. He had an excellent sustained response to IV lidocaine. Relevant literature on treatment of status like SUNCT/SUNA is briefly reviewed. IV lidocaine can be a very useful treatment for status like SUNA.